ANALISIS TINGKAT KEBERHASILAN USAHA USAHA KECIL MIKRO DAN MENENGAH DI KABUPATEN MALUKU TENGAH - Dientje Rumerung (Soso-Q : Jurnal Manajemen, 2018)
This study aims to determine the level of success of SMEs in Central Maluku District by deepening the factors that are considered dominant influence the level of success of SMEs business. The sample used in this research is 40 SMEs. The analytical tool used in this paper is the Multiple Liner Regression Method after passing the Classic assumption test so that the estimation conducted meets the criteria of regression analysis.The result of data processing shows that the capital has significant effect on the success of SMEs in Central Maluku Regency while the long variable of business has no effect. The results show that the accumulation of capital is very real determine the level of business success, because the greater the business capital will encourage the increasing scale of business from SMEs itself.Keywords: Capital, Old Business, Success Rate of Business.